Peculiar Features of Gas-Dynamic Processes in Pulsating Layer - I. A. Bokun; V I. Chernyshevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers an impulse structure of gas flow in low-frequency pulsating layer. An influence of pulsation frequency on layer resistance is taken into account in the paper.